(untitled) (Research, Society and Development, 2021)
Sliding hiatus hernias are uncommon in dogs and cats, although they are often described in humans. They can be classified into four types, with sliding hiatus hernia being the most prevalent in small animals. This condition can often lead to regurgitation and aspiration pneumonia, but it can also be asymptomatic. The purpose of this report is to describe a case of sliding hiatus hernia in a six-month-old Persian cat with regurgitation after stress. The patient was submitted to a simple radiographic exam, which showed no alterations, and contrasted radiography, in which it was possible to identify the protrusion of the stomach through the gastroesophageal junction. The treatment instituted was anti-inflammatory, antacid, and fractionation of food intake, aiming at the recovery of esophagitis and reducing gastric emptying time. Six months after diagnosis, the animal had no more clinical symptoms, and in a new imaging exam, it did not show protrusion of the stomach, thus concluding the efficacy in drug treatment and the importance of the contrasted radiography for diagnosis.